Pengaruh Produktivitas Perikanan Dalam Bidang Ekonomi Masyarakat - Zebua, Adeks Kristiani; Nisayangin, Nisayangin Mariana Daeli; Enjel, Enjel Delahowuhowu Telaumbanua (Jurnal Ilmu Pertanian dan Perikanan, 2024)
The development of the fisheries and marine sector is a big part that can influence the economic development of the domestic community as a whole, in increasing the growth of fisheries. Most of them lack effective and efficient processing. In this case, the role of the community in increasing the sustainability of fisheries productivity continuously is very large. The role of humans in managing nature is the basis for utilizing natural resources in the aquatic ecosystem. The research method used is a type of library research, namely research carried out by collecting data or scientific papers. The aim of the research is to simultaneously find out the benefits of a sustainable ecosystem, which can have a big influence on fisheries productivity which can create prosperity for the community, in building the economy and realizing the sovereignty of its economic activities.